Contribution des femmes a ladoption des varietes de mais tolerantes a la secheresse au Nord Benin - Baco, M.N.; Affoukouk, T.; Moumouni, I.; Yallou, C.; Abdoulaye, Tahirou (2014)
This study presents the results of a process of a participatory varietal selection of drought tolerate maize in districts of Kandi, Banikoara and Malanville. It was initiated to contribute to the debate on the adoption of innovations in relation to gender. The methodology used to collect and analyze data is based on the decentralization of research approaches. Three experimental sites, 60 farmers with 10 men and 10 women per site have participated in this stage of the participatory varietal selection. The sites of the experiments were located in the villages of Angaradebou (Kandi), Kokey (Banikoara) and Tomboutou (Malanville). The results of this work showed the importance of women throughout varietal selection process. With regard to the choice of the selection criteria, women didn’t only choose the same criteria as men, but they also identified a specific criterion to them which is the organoleptic quality. Regarding to the ranking of varieties seeds, women were more consistent (one variety has the highest score in the ranking of varieties and it is also the same that has the highest frequency in the varietal preference); which was not the case for men. These results showed the importance of women in appropriate technology choosing and the necessity to take into account their preference in the designing of new varieties.This study presents the results of a process of a participatory varietal selection of drought tolerate maize in districts of Kandi, Banikoara and Malanville. It was initiated to contribute to the debate on the adoption of innovations in relation to gender. The methodology used to collect and analyze data is based on the decentralization of research approaches. Three experimental sites, 60 farmers with 10 men and 10 women per site have participated in this stage of the participatory varietal selection. The sites of the experiments were located in the villages of Angaradebou (Kandi), Kokey (Banikoara) and Tomboutou (Malanville). The results of this work showed the importance of women throughout varietal selection process. With regard to the choice of the selection criteria, women didn’t only choose the same criteria as men, but they also identified a specific criterion to them which is the organoleptic quality. Regarding to the ranking of varieties seeds, women were more consistent (one variety has the highest score in the ranking of varieties and it is also the same that has the highest frequency in the varietal preference); which was not the case for men. These results showed the importance of women in appropriate technology choosing and the necessity to take into account their preference in the designing of new varieties.This study presents the results of a process of a participatory varietal selection of drought tolerate maize in districts of Kandi, Banikoara and Malanville. It was initiated to contribute to the debate on the adoption of innovations in relation to gender. The methodology used to collect and analyze data is based on the decentralization of research approaches. Three experimental sites, 60 farmers with 10 men and 10 women per site have participated in this stage of the participatory varietal selection. The sites of the experiments were located in the villages of Angaradebou (Kandi), Kokey (Banikoara) and Tomboutou (Malanville). The results of this work showed the importance of women throughout varietal selection process. With regard to the choice of the selection criteria, women didn’t only choose the same criteria as men, but they also identified a specific criterion to them which is the organoleptic quality. Regarding to the ranking of varieties seeds, women were more consistent (one variety has the highest score in the ranking of varieties and it is also the same that has the highest frequency in the varietal preference); which was not the case for men. These results showed the importance of women in appropriate technology choosing and the necessity to take into account their preference in the designing of new varieties.This study presents the results of a process of a participatory varietal selection of drought tolerate maize in districts of Kandi, Banikoara and Malanville. It was initiated to contribute to the debate on the adoption of innovations in relation to gender. The methodology used to collect and analyze data is based on the decentralization of research approaches. Three experimental sites, 60 farmers with 10 men and 10 women per site have participated in this stage of the participatory varietal selection. The sites of the experiments were located in the villages of Angaradebou (Kandi), Kokey (Banikoara) and Tomboutou (Malanville). The results of this work showed the importance of women throughout varietal selection process. With regard to the choice of the selection criteria, women didn’t only choose the same criteria as men, but they also identified a specific criterion to them which is the organoleptic quality. Regarding to the ranking of varieties seeds, women were more consistent (one variety has the highest score in the ranking of varieties and it is also the same that has the highest frequency in the varietal preference); which was not the case for men. These results showed the importance of women in appropriate technology choosing and the necessity to take into account their preference in the designing of new varieties.